Manejo Integrado del Cultivo de Mango Kent - Arce Calle, Bruce Ricardo Jhon Barnard; Granda Wong, Carlos Alberto; Javier Alva, Javier; San Martin Zapata, Carlos Enrique (Instituto Nacional de Innovación Agraria - INIA, 2019)
93 páginas.